Genetic basis of sudden death after COVID-19 vaccination in Thailand - Ittiwut, Chupong; Mahasirimongkol, Surakameth; Srisont, Smith; Ittiwut, Rungnapa; Chockjamsai, Manoch; Durongkadech, Piya; Sawaengdee, Waritta; Khunphon, Athiwat; Larpadisorn, Kanidsorn; Wattanapokayakit, Sukanya; Wetchaphanphesat, Suppachok; Arunotong, Surachet; et al. (Heart rhythm, 2022)
Severe acute respiratory syndrome coronavirus 2 vaccination reduces morbidity and mortality associated with coronavirus disease 2019 (COVID-19); unfortunately, it is associated with serious adverse events, including sudden unexplained death (SUD). We aimed to study the genetic basis of SUD after COVID-19 vaccination in Thailand. From April to December 2021, cases with natural but unexplained death within 7 days of COVID-19 vaccination were enrolled for whole exome sequencing. Thirteen were recruited, aged between 23 and 72 years; 10 (77%) were men, 12 were Thai; and 1 was Australian. Eight (61%) died after receiving the first dose of vaccine, and 7 (54%) died after receiving ChAdOx1 nCoV-19; however, there were no significant correlations between SUD and either the number or the type of vaccine. Fever was self-reported in 3 cases. Ten (77%) and 11 (85%) died within 24 hours and 3 days of vaccination, respectively. Whole exome sequencing analysis revealed that 5 cases harbored SCN5A variants that had previously been identified in patients with Brugada syndrome, giving an SCN5A variant frequency of 38% (5 of 13). This is a significantly higher rate than that observed in Thai SUD cases occurring 8–30 days after COVID-19 vaccination during the same period (10% [1 of 10]), in a Thai SUD cohort studied before the COVID-19 pandemic (12% [3 of 25]), and in our in-house exome database (12% [386 of 3231]). These findings suggest that SCN5A variants may be associated with SUD within 7 days of COVID-19 vaccination, regardless of vaccine type, number of vaccine dose, and presence of underlying diseases or postvaccine fever.